Az egészségügyi ágazati béremelés jogi aspektusai egy gyakorló munkajogász szemével - Bácsi, Mariann (Debreceni Jogi Műhely, 2014)
My essay analyses the rules of the wage-rise in the Hungarian health service system performed in two stages in 2012 and 2013. The difficulties of applying the rules and the continuous changes in the law are presented from a practical viewpoint.The personal and material scope of the raise in the health sector was the same circle: higher education institutions and religious institutions performing public mission that provide for in- and out-patient care. The wage-rise affected the employees having service relations with the above mentioned institutes in civil servant and commissionaire positions.In 2012 altogether86.000 persons benefitted from the raise (67.978 of them were directly involved in the healthcare), and 95.000 persons in 2013. The Act LXXXIV of 2003 distinguishes three groups of employees regarding the continuous and retroactive (ex post facto) raise of wages: doctors, graduates, pharmacists and health workers. In the case of these groups no uniformed wage scale exists, so different rules must be applied.The retroactive wager is in the case of the doctors depended on their salary, and the continuous rise was realized by a new wage scale. Other graduates and pharmacists gained a fixed rise. The retro active rise of the health workers was also fixed, the continuous wage rise was realized through a new wage scale and it depended whether their legal relation with the employer was established before or after the 1st of the July 2012.The complicated and frequently inaccurate regulation was corrected by the legislator, when a uniformed wage scale was directed to each group of employees in the September of 2013. A new sectoral wage scale was applied for the doctors and the health workers, and for other graduates and pharmacists the old public wage scale must be applied.Contrary to the uniformed regulation, there still remained legal institutions where the day/night duty, readiness, shift bonus, overtime must be specified according to the legislations in force on the 30th of June, 2012.Summing up, the legislator finally prevented the emigration of the highly qualified specialists by the execution of the wage rise in the last two years.